As situações de violência nos espaços das escolas: a voz dos alunos - Darido, Maira [UNESP]; Santos Filho, José dos Reis [UNESP] (My University, 2013)
The article aims to outline the situations of violence and vulnerability faced by young people in schools. To understand the scenario transposition of everyday violence for school spaces has become critical analysis of the phenomenon by a new perception in the voice of the students. Thus, from the application of semi-structured questionnaires for young people between 15 and 17 years was possible closer to the diagnosis. The notes, in the end, gave birth to a path of joint efforts between the school and the community providing refl ections on the subject.

O seguinte artigo buscou delinear as situações de violência e vulnerabilidade enfrentadas pelos jovens nas escolas. Para a compreensão do cenário de transposição da violência cotidiana para os espaços das escolas tornou-se fundamental a análise do fenômeno por uma nova percepção, sob a voz dos alunos. Assim, a partir da aplicação de questionários semiestruturados para jovens entre 15 e 17 anos foi possível uma maior aproximação com o diagnóstico. Os apontamentos, no limite, deram luz a um caminho de articulação de esforços entre a escola e a comunidade possibilitando refl exões acerca do tema.
Situations of violence in school spaces: the voice of students
Keywords: Violence; School; Teenagers; Violência; Escola; Adolescentes